Social representations of early motherhood among pregnant teenagers from North Central Mexico - Jiménez-Arroyo, Vanesa; Rangel-Flores, Yesica (Revista Chilena de Salud Pública, 2019)
Adolescent pregnancy represents a public health problem in Latin American countries. Limited understanding of local perceptions surrounding pregnancy and early motherhood contribute to the complexity of the phenomenon, which is seen as a problem by government officials, but may not be seen as such by the general population nor by affected adolescents. Thus, the objective of the research was to analyze pregnant adolescents’ social views of motherhood. A qualitative study focusing on social representations and gender perspective was conducted, and 13 adolescents from north central Mexico, who were pregnant with more than 20 weeks gestation and voluntarily accepted to participate, were interviewed. Transcribed interviews were analyzed using the Krueger method for content analysis. Results: Early motherhood is represented as an experience marked by guilt and fear, but also as a condition that provides meaning to adolescents who felt that their lives had been led off course prior to their pregnancies. It is important to note that several participants expressed feeling better when they were far from their partners, since they associated those relationships with violence and a loss of autonomy. Conclusions: The study identifies pregnant adolescents’ conceptualization of adolescent motherhood and allows for a more accurate estimation of the social risks that these women and their children face, not from a historical perspective but rather within a sociocultural context in which social representations are constantly being restructured.